Rendimento e composição de óleo essencial de lima ácida Tahiti (Citrus latifolia Tanaka) enxertada em 16 variedades de porta-enxertos - Costa, Gabriela da (2021)
It’s known that the canopy of the tree is responsible for the production and characteristics of the fruits, however the rootstock can have an influence, since the agronomic characteristics are the result of the interaction between both. Essential oils are products with high added value, due to their characteristics and bioactive molecules. They’re used in various industrial sectors. There is interest in expanding studies in this area. Therefore, the aim of this study was to determine the influence of rootstock varieties on yield and composition of the essential oil of Tahiti acid lime. Yield was evaluated in the two harvests (2017/2018) and vegetative development was evaluated in 2019. The hydrodistillation method was used for extraction of the essential oil and for quantification and identification of the components, analysis with GC-MS and GC-FID was used. As main results, the rootstock varieties that induced the greatest volume in the canopy of Tahiti IAC-5 acid lime were citrandarins H150, Rangpur lime, H121, H70, H145, H173 and H10. In the analysis of essential oils, yields per 100g of Tahiti acid lime peel ranged from 0.77 to 1.67%. Regarding the yield per hectare, citrandarin H10 induced a greater amount of oil per hectare in both crops. A total of 56 compounds were found, of which 48 showed significant differences in relative percentage. The major components were monoterpenes and monoterpenoids, such as limonene (30%), y-terpinene (11%), geranial (8.4%), β-pinene (6.5%) and neral (6.4%). Demonstrating influence of the rootstock on the composition and yield of essential oils.